Different roles with different goals: Designing to support shared situational awareness between patients and clinicians in the hospital. (5th November 2020) - Pollack, Ari H; Mishra, Sonali R; Apodaca, Calvin; Khelifi, Maher; Haldar, Shefali; Pratt, Wanda
Abstract: Objective: Team situational awareness helps to ensure high-quality care and prevent errors in the complex hospital environment. Although extensive work has examined factors that contribute to breakdowns in situational awareness among clinicians, patients' and caregivers' roles have been neglected. To address this gap, we studied team-based situational awareness from the perspective of patients and their caregivers. Materials and Methods: We utilized a mixed-methods approach, including card sorting and semi-structured interviews with hospitalized patients and their caregivers at a pediatric hospital and an adult hospital. We analyzed the results utilizing the situational awareness (SA) theoretical framework, which identifies 3 distinct stages: (1) perception of a signal, (2) comprehension of what the signal means, and (3) projection of what will happen as a result of the signal. Results: A total of 28 patients and 19 caregivers across the 2 sites participated in the study. Our analysis uncovered how team SA helps patients and caregivers ensure that their values are heard, their autonomy is supported, and their clinical outcomes are the best possible. In addition, our participants described both barriers—such as challenges with communication—and enablers to facilitating shared SA in the hospital. Discussion: Patients and caregivers possess critical knowledge, expertise, and values required to ensure successful and accurate team SA. Therefore, hospitals need to incorporate tools that facilitate patients and caregivers as key team members for effective SA. Conclusions: Elevating patients and caregivers from passive recipients to equal contributors and members of the healthcare team will improve SA and ensure the best possible outcomes.